2018
DOI: 10.2139/ssrn.3202937
|View full text |Cite
|
Sign up to set email alerts
|

RAD52 Prevents Excessive Replication Fork Reversal and Protects from Nascent Strand Degradation

Abstract: Stabilisation of stalled replication forks prevents excessive fork reversal and their pathological degradation, which can undermine genome integrity. Here we investigate a physiological role of RAD52 at stalled replication forks by using human cell models depleted of RAD52, a specific small-molecule inhibitor of the RAD52-ssDNA interaction, in vitro and singlemolecule analyses. We demonstrate that RAD52 prevents excessive degradation of reversed replication forks by MRE11. Mechanistically, RAD52 binds to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…It will be of interest to determine whether Rad52 in vertebrate organisms similarly protects DNA ends from extensive degradation. Recent study implicates that indeed human RAD52 could protect stalled replication forks from degradation (Malacaria et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to determine whether Rad52 in vertebrate organisms similarly protects DNA ends from extensive degradation. Recent study implicates that indeed human RAD52 could protect stalled replication forks from degradation (Malacaria et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mre11 Suppresses Oncogene-Induced R-Loops and DNA Damage The Mre11 complex suppresses the accumulation of spontaneous, replication-associated DSBs (Oh and Symington, 2018). In contrast, some studies have demonstrated that Mre11 nuclease activity can also promote destabilization of stalled replication forks (Malacaria et al, 2019;Schlacher et al, 2011). To determine whether Mre11 promotes or suppresses oncogene-induced DSBs in pMMECs, we measured gH2AX foci, 53BP1 foci, and neutral COMET tails (Figures 4A, 4B, and S4A).…”
Section: Mre11 Suppresses Oncogenic Proliferation Independently Of P53 and Atmmentioning
confidence: 99%
“…Importantly, this deregulated degradation of nascent DNA is also genetically dependent on fork remodeling, as regressed arms are mandatory entry points for DNA degrading enzymes 13 , 14 , 22 , 23 . Moreover, the HR protein RAD52 was recently shown to modulate fork stability and restart, by limiting SMARCAL1-dependent fork reversal or regulating reversed fork processing by MRE11 14 , 24 . Collectively, these recent observations have implicated the RAD51 recombinase and other HR factors both in the formation and in the stability of reversed replication forks 5 , 14 .…”
Section: Introductionmentioning
confidence: 99%